Embedding Social Innovation and Service Learning in Higher Education's Third Sector Policy Developments in Austria - Resch, Katharina; Fellner, Magdalena; Fahrenwald, Claudia; Slepcevic-Zach, Peter; Knapp, Mariella; Rameder, Paul (Frontiers in Education, 2020)
Social innovation in Austrian HEIs is discussed under the headline of their “Third Mission”. The HE sector is pressured to have more and more impact on society. Internationally speaking, many countries benefit from national policies and networks in the Third Sector, but policies in Austria were initiated only recently, in 2017, on a national level. Interestingly, the service learning approach as an innovative and socially responsible teaching methodology stands out in Austrian HE. This article classifies the developments of the Third Sector in Austria in the form of a policy brief. Austria has a growing community of practice in social innovation and service learning. The article gives insight into the strategic developments in Austria and is underpinned with recommendable action to be transferred to others.